Efectos de la victimización, percepción de riesgo y vulnerabilidad en el miedo al delito: un estudio en jóvenes universitarios mexicanos - Reyes-Sosa, Hiram; Puente-Martínez, Alicia; Páez, Darío; Castro-Angulo, Sughey (Pontificia Universidad Católica del Perú, 2025)
Violence and insecurity associated with drug trafficking have generated high levels of crime in Mexico. The latter has led to an increase in crime rates among society and, furthermore, to a large part of the population perceiving insecurity and victimization as two of the country’s main problems. This article proposes an explanatory and psychosocial model to study fear of crime in Mexico. In order to achieve this, the perspectives of victimization, risk perception and vulnerability are addressed. A total of 443 university students participated in the study (49.9% men and 50.1% women) with a mean of 21.32 years (SD = 2.23). The results showed that having been a victim of a crime (victimization) and the perceived risk perception (contextual) further promote concern about the crime. In relation to gender (vulnerability), it was found that women are more concerned than men about becoming a victim of a crime, particularly women perceive that the consequences of crime are more negative for their group of belonging.

A violência e a insegurança associadas ao tráfico de drogas têm gerado elevados níveis de criminalidade no México. Isto levou ao aumento das taxas de criminalidade na sociedade e, além disso, a que uma grande parte da população perceba a insegurança e a vitimização como dois dos principais problemas do país. Este artigo propõe um modelo explicativo e psicossocial para o estudo do medo do crime no México. Para tal, se tomaram as perspectivas de vitimização, percepção de risco e vulnerabilidade. O estudo envolveu 443 jovens estudantes universitários (49,9% homens e 50,1% mulheres) com uma idade média de 21,32 anos (DP = 2,23). Os resultados mostraram que ter sido vítima de crime (vitimização) e percepção de risco percebido (contextual) promovem a preocupação com o crime. As mulheres preocupam-se mais do que os homens em tornar-se vítimas de crime, particularmente as mulheres percebem que as consequências do crime são mais negativas para o seu grupo de pertença.

La violencia y la inseguridad asociada con el narcotráfico han generado altos niveles de delincuencia en México. Esto último, ha llevado a que los índices delictivos entre la sociedad vayan en aumento y, además, a que gran parte de la población perciba a la inseguridad y a la victimización como dos de los principales problemas del país. Este artículo propone un modelo explicativo y psicosocial para el estudio del miedo al delito en México. Para ello, se retomaron las perspectivas de la victimización, la percepción de riesgo y la vulnerabilidad. En el estudio participaron 443 jóvenes universitarios (49.9% hombres y 50.1% mujeres) con una media de 21.32 años (DT = 2.23). Los resultados mostraron que el hecho de haber sido víctima de un delito (victimización) y la percepción de riesgo percibida (contextual) promueven la preocupación por el delito. Las mujeres se preocupan más que los hombres por llegar a ser víctima de un delito, particularmente las mujeres perciben que las consecuencias del delito son más negativas para su grupo de pertenencia.
Effects of victimization, risk perception and vulnerability in the fear of crime: A study in Mexican university students
Os efeitos da vitimização, percepção de risco e vulnerabilidade no medo do crime: um estudo em jovens estudantes universitários mexicanos
Keywords: Fear of crime; Victimization; Risk perception; Vulnerability; Gender; Miedo al delito; Victimización; Percepción de riesgo; Vulnerabilidad; Género; Medo do crime; Vitimização; Percepção de risco; Vulnerabilidade; Gênero; https://purl.org/pe-repo/ocde/ford#5.01.00